2020
DOI: 10.2147/jpr.s272952
|View full text |Cite
|
Sign up to set email alerts
|

<p>DNA Microarray Analysis of Differential Gene Expression in the Dorsal Root Ganglia of Four Different Neuropathic Pain Mouse Models</p>

Abstract: Pathological stimuli or injury to the peripheral nervous system can trigger neuropathic pain with common clinical features such as allodynia and hypersensitivity. Although various studies have identified molecules or genes related to neuropathic pain, the essential components are still unclear. Therefore, in this study, we investigated the molecular and genetic factors related to neuropathic pain. Methods: We extracted candidate genes in the dorsal root ganglion (DRG) from three nerve injury mouse models and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Many studies have focused on investigating pain-associated gene expression changes in DRG. Microarray profiling and RNA-Seq have been widely employed to investigate the DRG transcriptome in many species such as mouse, rat, primate, and human (Chiu et al, 2014 ; Gong et al, 2016 ; Li et al, 2016 ; Barry et al, 2018 ; Ray et al, 2018 ; Megat et al, 2019a , b ; Yokoyama et al, 2020 ; Kupari et al, 2021 ). Among these reports, some assessed mRNA levels specifically in Na V 1.8-expressing (Na V 1.8 + ) nociceptors.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have focused on investigating pain-associated gene expression changes in DRG. Microarray profiling and RNA-Seq have been widely employed to investigate the DRG transcriptome in many species such as mouse, rat, primate, and human (Chiu et al, 2014 ; Gong et al, 2016 ; Li et al, 2016 ; Barry et al, 2018 ; Ray et al, 2018 ; Megat et al, 2019a , b ; Yokoyama et al, 2020 ; Kupari et al, 2021 ). Among these reports, some assessed mRNA levels specifically in Na V 1.8-expressing (Na V 1.8 + ) nociceptors.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, neuropathic pain is one of the chronic pains which is often triggered by PNI and caused by damage to the somatosensory nervous system, with common clinical features such as mechanical allodynia. Neuropathic pain is challenging to cure, and there is currently no known cure ( 51 , 52 ). DRG is widely recognized as a potential target for the treatment of chronic pain due to its ability to transmit harmful stimulus information to the cerebral cortex ( 53 , 54 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the peripheral nervous system, a previous study showed that AVP upregulates the function of GABA A in dorsal root ganglion neurones 39 . Furthermore, DNA microarray analysis revealed that the V1a receptor was upregulated in a mouse model of NP 40 . Subcutaneous plantar injection of AVP was shown to attenuate formalin-induced nociceptive pain via peripheral V1a receptors 6 .…”
Section: Discussionmentioning
confidence: 99%